2016
DOI: 10.5815/ijmsc.2016.04.04
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Approach based on Classification and Clustering for Intrusion Detection System

Abstract: Computer security plays an important role in everybody's life. Therefore, to protect the computer and sensitive information from the untrusted parties have great significance. Intrusion detection system helps us to detect these malicious activities and sends the reports to the administration. But there is a problem of high false positive rate and low false negative rate. To eliminate these problems, hybrid system is proposed which is divided into two main parts. First, cluster the data using K-Mean algorithm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…It is very important for network protection and control to detect intrusion attacks effectively [17]. In the network intrusion detection, clustering algorithm [18], Apriori algorithm, decision tree [19], Q-learning, neural network [20] and hidden Markov [21] have a wide range of applications. This study mainly analyzed SVM.…”
Section: Discussionmentioning
confidence: 99%
“…It is very important for network protection and control to detect intrusion attacks effectively [17]. In the network intrusion detection, clustering algorithm [18], Apriori algorithm, decision tree [19], Q-learning, neural network [20] and hidden Markov [21] have a wide range of applications. This study mainly analyzed SVM.…”
Section: Discussionmentioning
confidence: 99%
“…In literature review, we found that there are many ensemble classifiers which have been used for intrusion detection system. Jasmeen K. Chahal and Amanjot Kaur [8] have proposed hybrid intrusion detection to improve false positive and false negative rate. Authors have used K-mean algorithm for clustering data and adaptive Support Vector Machine for classification purpose.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of that, the cyber space is becoming an unsafe place day by day due to malicious activities. These malicious activities are also called as intrusions that effect integrity, confidentiality and availability of resources [1]. Intrusion detection system (IDS) is a system which protects resources against intrusions.…”
Section: Introductionmentioning
confidence: 99%